2016
DOI: 10.1158/1078-0432.ccr-15-3103
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Subclonal and Clonal Gene Mutations before and after Therapy in Chronic Lymphocytic Leukemia

Abstract: Purpose: Chronic lymphocytic leukemia (CLL)-associated gene mutations that influence CLL cell fitness and chemotherapy resistance should increase in clonal representation when measured before therapy and at relapse.Experimental Design: To uncover mutations associated with CLL relapse, we have performed whole-exome sequencing in a discovery cohort of 61 relapsed CLL patients identifying 86 recurrently mutated genes. The variant allele fractions (VAF) of 19 genes with mutations in !3 of 61 cases were measured in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 50 publications
1
52
0
Order By: Relevance
“…The CLL cases selected for this study were highly characterized for known clinically relevant traits. In addition, the relapsed CLL samples were analyzed for gene mutations through whole exome sequencing (WES) and subsequent Sanger sequencing of all recurrently mutated genes as detected through WES, SNP 6.0 profiling of genomic copy number changes and deep panel-based gene re-sequencing of TP53, NOTCH1 and other genes as described(28). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLL cases selected for this study were highly characterized for known clinically relevant traits. In addition, the relapsed CLL samples were analyzed for gene mutations through whole exome sequencing (WES) and subsequent Sanger sequencing of all recurrently mutated genes as detected through WES, SNP 6.0 profiling of genomic copy number changes and deep panel-based gene re-sequencing of TP53, NOTCH1 and other genes as described(28). …”
Section: Resultsmentioning
confidence: 99%
“…Solution-based exome capture and HiSeq2000-based massively parallel sequencing and bioinformatic pipeline analysis of WES data was performed as described(28). …”
Section: Methodsmentioning
confidence: 99%
“…It was shown that 3-5% of CLL patients have acquired mutations in SAMHD1 at diagnosis (Clifford et al, 2014). However, SAMHD1 mutation frequency is increased in relapsed/refractory CLL (9-11%) without associated increase of other poor risk factors, such as 11q deletion or unmutated IGHV (Clifford et al, 2014;Amin et al, 2016). Two independent studies associated SAMHD1 mutations with resistance to standard CLL therapies (Clifford et al, 2014;Amin et al, 2016).…”
Section: Cell Cycle Apoptosis and Dna Damage And Synthesismentioning
confidence: 99%
“…However, SAMHD1 mutation frequency is increased in relapsed/refractory CLL (9-11%) without associated increase of other poor risk factors, such as 11q deletion or unmutated IGHV (Clifford et al, 2014;Amin et al, 2016). Two independent studies associated SAMHD1 mutations with resistance to standard CLL therapies (Clifford et al, 2014;Amin et al, 2016). Indeed, standard treatments may select pre-existing clones carrying SAMHD1 mutations (Amin et al, 2016).…”
Section: Cell Cycle Apoptosis and Dna Damage And Synthesismentioning
confidence: 99%
“…Whole‐exome sequencing (WES) has led to the discovery of mutations in genes such as SF3B1 , which encodes a protein that normally acts as part of the RNA spliceosome and mRNA processing machinery, with a reported mutational frequency in CLL between 10–15% (Wang et al , ; Wan & Wu, ). While functional loss or gain within the mutation is currently unclear, SF3B1 mutations cause deleterious effects on DNA damage repair and are associated with a shorter time‐to‐first treatment (TTFT) and overall survival (OS) (Jeromin et al , ; Te Raa et al , ; Amin et al , ; Nadeu et al , ). Additional examples include mutations in TP53, BIRC3, ATM, KRAS, POT1 and NOTCH1, which were all associated with reduced responses to treatment and shorter survival (Rossi et al , ; Cortese et al , ; Landau et al , ; Herling et al , ; Nadeu et al , ).…”
mentioning
confidence: 99%